Cassandra the lucky - Holub, Joan; Williams, Suzanne (New York : Aladdin, 2013)
Despite the fact that no one ever believes her prophecies, Cassandra is determined to help people make their own luck. When she sends some special fortunes to the Mount Olympus Academy, the prophecies come true, but in unexpected ways.
Ages 8-12.
Keywords: Mythology, Greek -- Juvenile fiction; Fantasy fiction